Mechanism of action of two insect toxins huwentoxin-III and ainantoxin-VI on voltage-gated sodium channels - Wang, Rui-lan (Zhejiang University Press, 2010)

(untitled)
Selenocosmia huwena and Selenocosmia hainana are two tarantula species found in southern China. Their venoms contain abundant peptide toxins. Two new neurotoxic peptides, huwentoxin-III (HWTX-III) and hainantoxin-VI (HNTX-VI), were obtained from the venom using ion-exchange chromatography and reverse-phase high performance liquid chromatography (RP-HPLC). The mechanism of action of HWTX-III and HNTX-VI on insect neuronal voltage-gated sodium channels (VGSCs) was studied via whole-cell patch clamp techniques. In a fashion similar to δ-atracotoxins, HNTX-VI can induce a slowdown of current inactivation of the VGSC and reduction in the peak of Na(+) current in cockroach dorsal unpaired median (DUM) neurons. Meanwhile, 10 µmol/L HNTX-IV caused a positive shift of steady-state inactivation of sodium channel. HWTX-III inhibited VGSCs on DUM neurons (concentration of toxin at half-maximal inhibition (IC(50))≈1.106 µmol/L) in a way much similar to tetrodotoxin (TTX). HWTX-III had no effect on the kinetics of activation and inactivation. The shift in the steady-state inactivation curve was distinct from other depressant spider toxins. The diverse effect and the mechanism of action of the two insect toxins illustrate the diverse biological activities of spider toxins and provide a fresh theoretical foundation to design and develop novel insecticides.